A Review of Orbital Friction Stir Welding - Francisco B. Ferreira; Igor Felice; Isaque Brito; João Pedro Oliveira; Telmo Santos (Metals, 2023)
Friction stir welding is a solid-state joining process widely used in several industrial applications. One of its variants, orbital friction stir welding, is of key importance in fundamental industries such as oil and gas and aerospace. For orbital friction stir welding, there is a need to develop not only new process parameters but also tools and ancillary mechanisms that can ensure sound, high-performing joints are obtained. This review assesses the current state of orbital friction stir welding, highlighting several key aspects related to this technology.